2008
DOI: 10.1007/s10147-008-0787-x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical complications of salvage total laryngectomy following concurrent chemoradiotherapy

Abstract: There was an increased risk of wound complications in patients undergoing salvage laryngectomy following CCRT. Patients who developed pharyngocutaneous fistulas after CCRT tended to require surgical reintervention for repair. These findings should be taken into account before the initiation of CCRT and salvage surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 18 publications
(27 reference statements)
6
67
3
Order By: Relevance
“…In other studies [18,[25][26][27][28] mean time of restoration a normal feeding was 25 days and in Pellini's study was in less than 1 month for 61.5 % of patients [22]. The time of removal of the feeding tube ranged in literature from 10-96 days [28] to 12-90 days [18], in our study was 4-230 days.…”
Section: Complications and Functional Resultssupporting
confidence: 39%
“…In other studies [18,[25][26][27][28] mean time of restoration a normal feeding was 25 days and in Pellini's study was in less than 1 month for 61.5 % of patients [22]. The time of removal of the feeding tube ranged in literature from 10-96 days [28] to 12-90 days [18], in our study was 4-230 days.…”
Section: Complications and Functional Resultssupporting
confidence: 39%
“…Prior radiotherapy influences wound healing and increases the risk of developing wound complications; the role of concomitant chemotherapy, however, is not known. Furuta et al [14] compared the surgical complication rates of total laryngectomy with preoperative treatment. They noted an increase in the frequency and severity of wound complications in patients who underwent salvage total laryngectomy after CCRT, but this was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…While some authors have found that the complication rate for salvage surgery after chemoradiotherapy is higher than that after radiotherapy alone [7][8][9], others report no significant differences [10][11][12].…”
Section: Introductionmentioning
confidence: 92%